#### Answer

y = $\frac{-2 - 3x}{-6}$

#### Work Step by Step

Solve for y by isolating it to one side of the equation:
3x - 6y = -2
Subtract 3x:
-6y = -2 - 3x
Divide both sides by -6:
y = $\frac{-2 - 3x}{-6}$

Published by
Pearson

ISBN 10:
0321726391

ISBN 13:
978-0-32172-639-1

y = $\frac{-2 - 3x}{-6}$

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.